Effect of social aspects of the classroom climate on Grades 3–6 students’ perceptions of the emotional classroom climate in primary school mathematics lessons - Kuzle, Ana (Teaching Mathematics and Computer Science, 2026)
Current research efforts highlight the significance of the social climate in the classroom. This climate influences not only students’ academic performance, motivation, engagement, and participation, but also their perception of the emotional classroom climate. However, little attention has been given to the effects of the various social aspects of the classroom climate on students’ perceptions of the emotional classroom climate. The present study addressed this gap by investigating aspects of the social classroom climate as possible explanatory factors of a positive, negative or ambivalent students’ perception of the emotional classroom climate in Grades 3–6 mathematics lessons. The secondary analysis of participant-produced drawings revealed that in drawings depicting a positive emotional classroom climate, the teacher provided assistance and made the lesson goals clear. Furthermore, the students talked to each other about mathematics. Conversely, in drawings depicting a negative emotional classroom climate, the teacher made behavioral requests, and negative student-student communication was present. Both the working method and the classroom seating arrangement did not seem to affect the perceived emotional classroom climate. The results are discussed in terms of their theoretical, and practical implications.Subject Classification: 97C20